1990
DOI: 10.1002/ar.1092260114
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐sectional internal diameters of human cervical and femoral blood vessels: Relationship to subject's sex, age, body size

Abstract: Cross-sectional internal diameter measurements were made of right and left common carotid and right femoral arteries and right and left internal jugular, superficial femoral, and common femoral veins in 32 normal human subjects utilizing duplex ultrasonography. The relationships of these vessel sizes to the subject's sex, age, height, weight, and body surface area were analyzed statistically; and graphs were constructed, indicating the relationship of blood vessel diameters to the various body size parameters.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
65
2

Year Published

1993
1993
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(77 citation statements)
references
References 5 publications
7
65
2
Order By: Relevance
“…The rate of accidental carotid artery puncture was also higher among children <16.3 kg in both US (15.4 vs. 3.0%) and LM groups (24.5 vs. 12.5%), compared to children >16.3 kg (13). The difficulty in achieving successful cannulation among neonates can be attributed in part to the small diameter of the vessels, making it difficult to locate even under US visualization (17). Mortensen et al (17) reported correlations between body weight and surface area with vein diameter, with a stronger correlation for femoral veins compared to internal jugular veins.…”
Section: Discussionmentioning
confidence: 95%
“…The rate of accidental carotid artery puncture was also higher among children <16.3 kg in both US (15.4 vs. 3.0%) and LM groups (24.5 vs. 12.5%), compared to children >16.3 kg (13). The difficulty in achieving successful cannulation among neonates can be attributed in part to the small diameter of the vessels, making it difficult to locate even under US visualization (17). Mortensen et al (17) reported correlations between body weight and surface area with vein diameter, with a stronger correlation for femoral veins compared to internal jugular veins.…”
Section: Discussionmentioning
confidence: 95%
“…There may be diagnostic problems in pediatric patients who present with phlebectasia mimicking other neck masses [5,6]. In the literature, there are many studies about the sizes and cross-sectional area of the IJV, aiming at guiding both the interventional medical procedures and also the diagnosis of vascular pathologies like phlebectesia [1,2,[7][8][9][10]. Mortensen et al [1] measured the cross-sectional internal diameters of IJVs in a study they performed in cervical and femoral vessels.…”
Section: Introductionmentioning
confidence: 97%
“…In the literature, there are many studies about the sizes and cross-sectional area of the IJV, aiming at guiding both the interventional medical procedures and also the diagnosis of vascular pathologies like phlebectesia [1,2,[7][8][9][10]. Mortensen et al [1] measured the cross-sectional internal diameters of IJVs in a study they performed in cervical and femoral vessels. Jeon et al [9] compared the diameters of internal jugular phlebectasia with diameters of IJVs in normal children.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The IJV is of variable size in adults and correlates poorly with other measurable physiological dimensions such as neck circumference. Internal jugular vein diameter has been shown to be weakly related to that of the femoral vein [4], but this observation is of limited use in the clinical situation. It has been stated that the external jugular vein (EJV) bears an inverse relationship in size to the other veins in the neck [5].…”
mentioning
confidence: 99%